An integrated understanding of the immunology of allograft inflammation. Issue 2 (April 2017) - Houlihan, Brenna; Cha, Priscilla; Zasloff, Michael; Fishbein, Thomas M.; Kroemer, Alexander
Abstract : Purpose of review: The purpose of this review is to summarize recent advances in our understanding of the complex immunology of intestinal transplantation and allograft rejection. Recent findings: Recent findings highlight the importance of the intestinal microbiome for intestinal homeostasis and the role of newly discovered innate lymphoid cells in intestinal transplantation. In addition, the role of host antimicrobial Th17 responses in the pathogenesis of inflammatory bowel diseases and intestinal allograft rejection has been further elucidated. Summary: Research on the complex immune system of the intestine has continued to reveal more intricacies and connections with each study performed, making treatment of intestinal transplant patients more multifaceted. The interaction, communication, and relationships between areas such as the microbiome, innate lymphoid cells, and Th17 cells reveal possible targets for therapy and further areas requiring ongoing research.